Physical properties of chia (Salvia hispanica L.) seeds - Ixtaina, Vanesa Yanet (2008)
Physical properties of Salvia hispanica L. seeds were investigated and their application was also discussed. Physical properties were assessed for white and dark seed separately, except for the angle of repose and static coefficient of friction, which were determined for the seed mixture. The mean moisture content was 7.0% (dry basis). The average for the three characteristic dimensions, length, width and thickness was 2.11, 1.32 and 0.81 mm for dark seeds and 2.15, 1.40 and 0.83 mm for white seeds, respectively. The bulk density, true density and the porosity were between 0.667 and 0.722 g cm-3, 0.931 and 1.075 g cm-3, and 22.9 and 35.9%, respectively. The equivalent diameter ranged from 1.32 to 1.39 mm. The volume of single grain and sphericity ranged between 1.19 and 1.42 mm3, and 62.2 and 66.0%, respectively. The geometric mean diameter ranged between 1.31 and 1.36 mm for dark and white chia seeds, respectively. This parameter could be used for the theoretical determination of seed volume and sphericity. One thousand seed mass averaged 1.323 g for dark seeds, and 1.301 g for white seed. The angle of repose varied between 16° and 18° whereas the value of static coefficient of friction was 0.28 on galvanized sheet and 0.31 on mild steel sheet.